IMPLEMENTATION OF THE ENTREPRENEURIAL VISION OF MAKASSAR STATE UNIVERSITY THROUGH UNM ALUMNI ENTREPRENEURSHIP ACTIVITIES - Gita Irawanda; Andi Ratu Ayuashari Anwar; Tri Agung Nusantara Kr. J. Tompong (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe the understanding of Universitas Negeri Makassar (UNM) alumni regarding the university’s entrepreneurial vision, identify its implementation in their businesses, analyze supporting and inhibiting factors, and examine its contribution to personal and professional competence development. Employing a descriptive qualitative approach with a phenomenological perspective, data were collected through in-depth interviews, observations, and documentation with five alumni who actively run businesses. Data were analyzed using Miles et al.’s (2014) interactive model consisting of data reduction, display, and verification. The findings indicate that alumni understand UNM’s entrepreneurial vision, although the depth of understanding varies and tends to increase after engaging directly in business activities. The vision’s implementation is reflected in diverse sectors, including education, fashion, culinary, and creative services, with adaptive strategies utilizing social media and alumni networks. Supporting factors include theoretical knowledge from coursework, lecturer guidance, family support, and technology access, while key obstacles involve limited capital, lack of post-graduation mentoring, and intense market competition. Entrepreneurial experience contributes to the development of technical and non-technical skills and the creation of new jobs. These results highlight the importance of institutional support in strengthening the implementation of the entrepreneurial vision through continuous alumni development programs.